PERANCANGAN FILM PENDEK BERJUDUL “MUDAHNYA MEMBACA” TENTANG GERAKAN LITERASI NASIONAL PADA REMAJA - Martinus Eko Prasetyo; S Inesia Linando; Asrullah Ahmad (JURNAL Dasarrupa: Desain dan Seni Rupa, 2023)
Cultural changes in Indonesia make the literacy level of Indonesian adolescents low so that teenagers have less interest in reading. Due to the lack of short film media that raises literacy in Indonesia, the author designed a short film with an interesting story composition and good audio-visual delivery so that the message he wanted to convey was conveyed. However, this research aims to design short films in the form of entertainment media for teenagers to realize the low reading level in Indonesia. This research method uses descriptive qualitative methods by collecting data obtained from the method of observation, literature study, and questionnaires. The design method used in this paper is the stage of development, pre-production, production, post-production and distribution. The results of this study are an explanation of the creative strategies used in making short films, and a discussion of the pre-production, production, and post-production processes in a short film entitled "Mudahnya Membaca".